2019
DOI: 10.3390/mti3010021
|View full text |Cite
|
Sign up to set email alerts
|

Improving Driver Emotions with Affective Strategies

Abstract: Drivers in negative emotional states, such as anger or sadness, are prone to perform bad at driving, decreasing overall road safety for all road users. Recent advances in affective computing, however, allow for the detection of such states and give us tools to tackle the connected problems within automotive user interfaces. We see potential in building a system which reacts upon possibly dangerous driver states and influences the driver in order to drive more safely. We compare different interaction approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…Zhu et al [65] and Fakhrhosseini et al [16] investigated the use of music to relieve anger situations while driving. Braun et al explored the viability of ambient light, visual feedback, voice interaction, and an empathic voice assistant as strategies to regulate sadness and anger while driving [6]. Nass et al investigated mirroring voice with driver emotions and found that when drivers' emotions matched the car's voice emotion, they had fewer accidents, focused more on the road and spoke more to the car [41].…”
Section: In-car Responses To Regulate and Influence Emotionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al [65] and Fakhrhosseini et al [16] investigated the use of music to relieve anger situations while driving. Braun et al explored the viability of ambient light, visual feedback, voice interaction, and an empathic voice assistant as strategies to regulate sadness and anger while driving [6]. Nass et al investigated mirroring voice with driver emotions and found that when drivers' emotions matched the car's voice emotion, they had fewer accidents, focused more on the road and spoke more to the car [41].…”
Section: In-car Responses To Regulate and Influence Emotionsmentioning
confidence: 99%
“…doors open, car locked), or as reading lights (for example, BMW Moodlight 5 ). Outside the car, ambient lighting is also used in other road environments such as tunnels 6 . This familiarity makes it a useful and suitable modality to augment the car's interior with further information that can easily be perceived by the driver.…”
Section: Emotion Feedback: In-car Ambient Lightmentioning
confidence: 99%
“…This approach has the advantages of being adaptive to various driving situations, drivers' propensities and coping strategies, and the uncertainty of traffic behaviors [62]. Recent findings suggest that, in addition to matching vehicle voice to driver's affect, vehicle voice showing empathy via a voice assistant led to the largest improvement of negative emotions and was also positively perceived by angry and sad drivers [63].…”
Section: Measuring Affect To Improve Driver-vehicle Interactionsmentioning
confidence: 99%
“…The first article [16] investigates the characteristics of in-vehicle voice agents to increase technology acceptance and improve upon the perceived ease of use of automated vehicle technology. The next article [17] addresses the issue of driver emotions that may have a negative influence on road safety, and the authors suggest employing affective computing for emotional state detection and parametrization of empathic digital assistants to improve driver emotions and, as a consequence, enable safer driving. The authors of the third article [18] focus (again) on the effect of feedback on the perceived ease of use when interacting with automated driving systems at lower levels of automation (Society of Automotive Engineers (SAE) Levels 0-3) and conclude that the perceived ease of use can be used as a diagnostic measure in interaction with automated vehicles.…”
Section: Summary Of Contributionsmentioning
confidence: 99%
“…The basic assumption of the authors in "Improving Driver Emotions with Affective Strategies" [17] is that sad or angry drivers are prone to perform worse at driving which, in turn, decreases overall road safety. To counteract, Braun et al suggest using affective computing tools and methods for the detection of drivers' (negative) emotional states.…”
Section: Summary Of Contributionsmentioning
confidence: 99%